Instant Leaders in the Perspective of Herbert Blumer's Symbolic Interactionism Theory - Agnia, Wini; Alfiandi, Bob; Afrizal, Afrizal (Jurnal Ilmu Sosial dan Ilmu Politik (JISIP), 2025)
This study aims to explain instant leaders based on the phenomenon of Kaesang becoming the General Chairperson of the Partai Solidaritas Indonesia according to students, a study of 10 Law students from Andalas University, class of 2023. The research method used is qualitative, and the data collection process is carried out through in-depth interviews. This study's analysis unit is the individual analysis unit, namely, students who are new voters in the election. The researcher used qualitative analysis techniques to analyze the data. The theory used in this study is the symbolic interactionism theory proposed by Herbert Blumer. The results of the study explain that instant leaders in the perspective of this theory are classified into three premises of Herbert Blumer, namely (1) the meaning of instant leaders according to students, based on students' understanding of instant leaders, students' perceptions of Kaesang becoming the Chairperson of PSI, the effectiveness of instant leadership according to students, and the classification of ideal leaders according to students; (2) social interaction in the formation of the meaning of instant leaders, based on information media, formal education, and student political behavior; and (3) reconstructing the meaning of instant leaders by students, based on the influence of media, academic environment, and organizations.